Memory Against Forgetting : Memoir of a Time in South African Politics 1938 - 1964 - Bernstein, Rusty (Book collections on Project MUSE., 2017)
Lionel 'Rusty' Bernstein was arrested at Liliesleaf Farm, Rivonia, on 11 July 1963 and tried for sabotage, alongside Nelson Mandela, Walter Sisulu, Govan Mbeki and other leaders of the African National Congress and Umkhonto we Sizwe in what came to be known as the Rivonia Trial. He was acquitted in June 1964, but was immediately rearrested. After being released on bail, he fled with his wife Hilda into exile, followed soon afterwards by their family. This classic text, first published in 1999, is a remarkable man's personal memoir of a life in South African resistance politics from the late 1930s to the 1960s. In recalling the events in which he participated, and the way in which the apartheid regime affected the lives of those involved in the opposition movements, Rusty Bernstein provides valuable insights into the social and political history of the era.